Microplastics Desorption From Green Mussels (Perna viridis L., 1758) Using Oxidizing Agent Ca(OH)2 - Putri, Lily Surayya Eka; Mardiansyah, Mardiansyah; Yulia, Anis (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2025)
Microplastics (MPs) are currently one of the main pollutants in the aquatic environment and translocation to the human body will cause health problems. This study aims to find the desorption formula for MPs from green mussels (Perna viridis) with the oxidizing agent Ca(OH)2 or whiting lime. The results will be compared with the use of HNO3 which is commonly used for MPs analysis. There were 2 variations of Ca(OH)2, namely 10 and 15 mL, and soaking for 15; 30; and 60 minutes. The abundance and characteristics of MPs (shape, size, and color) were observed in 30 samples with 3 repetitions. The results of this research indicate that all samples have been contaminated with MPs. The highest number of MPs was found in the immersion of Ca(OH)2 for 30 minutes at a concentration of 15 mL of 1% Ca(OH)2. The oxidizing agent Ca(OH)2 was able to remove MPs much higher than HNO3 with an effectiveness of 72.98–1,120% or 2–12 times, which was supported by statistical results that showed significant differences (P <0.05). Thus, the conclusion is that the use of Ca(OH)2 is effective in removing MPs from green mussels with an optimal ratio of 1:3.8 (g/mL).